Perancangan Aplikasi Pencarian Undang Undang Otonomi Khusus Aceh (Qanun) Berbasis Android Menggunakan Metode Algoritma Berry Ravindran - Sahminul Sahminul (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
Qanun is a set of rules that have binding power and force Muslims to carry out the rules or laws. there are still many people who do not know about the existing rules in the area of ​​Aceh, the understanding of qanun and the sentence imposed for violating the qanun, the use of books is also considered to be long enough in the search for articles on the qanun, so it requires a long process of determining the sentence imposed for the actions of violators of the qanun. Berry Ravindran's algorithm works in two phases, namely the preprocessing phase and the search phase and start pattern matching from left to right. This algorithm is often implemented in various string search functions, such as for Find and Replace functions, DNA matching, and so on. For the preprocessing phase, a calculation is performed to determine the number of shifts and after that a search phase is carried out by matching strings from left to right. If there is a mismatch, the pattern will be shifted according to the rules of the Berry Ravindran algorithm. The author hopes to be able to know the special law of Aceh qanun based on mobile devcie. and Facilitate the search for Aceh qanun. And so that the public can know the law in Aceh, only by using an Android-based mobile device that already has a special law search application for Aceh qanun